Observation On The Induced Spawning Practices In The Hatcheries Of Rajshahi District Of Bangladesh (Journal of Life and Earth Science, 2012)
An investigation was conducted during the period from March to December 2009 to investigate the induced spawning practices in 22 hatcheries of 6 Upazilas of Rajshahi District of Bangladesh. It was observed that, 6 native fish species viz. rui (Labeo rohita), catla (Catla catla), mrigal (Cirrhina mrigala), calibaush (Labeo calbasu), bata (Labeo bata), gonia (Labeo gonius) and six exotic fish species such as silver carp (Hypophthalmichthys moltrix), bighead carp (Aristichthys nobilis), grass carp (Ctenopharyngodon idella), common carp (Cyprinus carpio), Thai pangus (Pangasius sutchi), rajputi (Puntius gonionotus) were used in the surveyed hatcheries for induced spawning purpose. The average length limit was 41.70±13.02 to 72.81±25.98 cm, average age limit was 1.96±0.75 to 3.08±0.90 years and average weight limit was 1.83±0.79 to 7.54±3.92 kg of the brood fish. Two types of hormone injections like PG (pituitary gland) and HCG (human chorionic gonadotropin) were used for induced spawning. The rate of 1st doses of injections of PG were from 1 to 4 mg/kg and HCG from 150 to 500 IU/kg and the rate of 2nd doses of injections of PG for native and exotic species were from 4 to 8 mg/kg and 4 to 10 mg/kg respectively. The incubation period and hatching rate in different fish species varied from 10 to 72 hours and 55% to 80%, respectively. DOI: http://dx.doi.org/10.3329/jles.v6i0.9723 JLES 2011 6: 65-68